Association of Prior Left Ventricular Ejection Fraction with Clinical Outcomes in Patients with Heart Failure with Midrange Ejection Fraction - Alison Brann (2020)
© 2020 American Medical Association. All rights reserved. Importance: Patients categorized as having heart failure (HF) with left ventricular ejection fraction (LVEF) in the midrange between 40% and 50% (HFmrEF) are known to be at increased risk of future events. Although patients can transition into the midrange through either improvement or deterioration in their LVEF, there is limited information available assessing the association of directional change in LVEF with future events. Understanding the association between change in LVEF and the clinical course of patients with HFmrEF would be of value in guiding management strategies. Objective: To determine whether risk of clinical events experienced by patients with HFmrEF varies according to whether LVEF improved or deteriorated into the range of 40% to 50% from previous measurements. Design, Setting, and Participants: In this retrospective cohort study, patients were identified from the electronic health records at the UC San Diego Health System who had an LVEF measured between 40% and 50% on transthoracic echocardiography (TTE) performed during the calendar year of 2015 and who also had at least 1 prior TTE for comparison. The clinical course of these patients was then followed from the time of the index TTE through December 2018. Data were analyzed from January to March 2019. Main Outcomes and Measures: The composite of all-cause mortality and all-cause hospitalization, the composite of cardiovascular mortality and HF hospitalization, and each of the individual components. Results: Of the 448 patients who were identified with HFmrEF, 278 (62.1%) were male, and the mean (SD) age was 67.4 (9.7) years. Left ventricular ejection fraction improved from less than 40% in 157 patients (35.0%), deteriorated from greater than 50% in 224 patients (50.0%), and remained between 40% and 50% over time in 67 patients (15.0%). Compared with patients whose LVEF improved from less than 40% to midrange levels, patients whose LVEF deteriorated from greater than 50% had higher risk of all-cause mortality and hospitalization (hazard ratio, 1.34; 95% CI, 1.10-1.82; P =.03) and of cardiovascular mortality and HF hospitalization (hazard ratio, 1.71; 95% CI, 1.08-2.50; P =.02), and these differences persisted after multivariable analysis. Outcomes did not differ significantly between patients whose LVEF improved and those in whom it remained stable. Conclusion and Relevance: In a cohort of patients with HFmrEF from a large academic medical center, the clinical course was strongly influenced by the directional change in LVEF from prior study. Patients whose LVEF deteriorated into midrange levels experienced a significantly higher risk of adverse clinical events than patients whose LVEF had improved. These results suggest that directional change in LVEF from prior measurements should be considered when devising management strategies for patients with HFmrEF..